Some biochemical parameters and oxidative stress biomarkers in sheep with paratuberculosis - Balikci, Engin; Gurdogan, Fuat (Polish Soc Veterinary Sciences Editorial Office, 2015)
The aim of this study was to investigate the oxidative stress biomarkers and some biochemical parameters for subclinical and clinical paratuberculosis in sheep. A number of 24 sheep positive for ELISA and PCR were categorized into 2 classes. According to the results of biochemical parameters, total protein, albumin, Ca and Mg levels of the diseased sheep decreased significantly (P <0.05) in clinical and subclinical groups when compared to the control group. Total protein, albumin, Ca and Mg levels decreased significantly (P < 0.05) in the clinical group when compared to the subclinical group. No significant difference was observed for globulin, glucose, BUN, creatinine, total bilirubine, total cholesterol and triglycerides levels in both subclinical and clinical cases compared to control sheep. The levels of SOD, GSH-Px and GSH decreased significantly (P < 0.05) in clinical and subclinical groups compared to the control group. The plasma level of TBARS increased significantly (P < 0.05) in clinical and subclinical groups compared to the control group. Conclusively oxidative stress and some biochemical parameters could be used as novel biomarkers in differential diagnosis of clinical and subclinical paratuberculosis in sheep.
Keywords: Paratuberculosis; oxidative stress; biochemical parameters; sheep